Epidemiological, clinical and imaging features of patients with microcephaly and suspected infection by Zika virus. Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga (Boletin Médico de Postgrado, 2020)
Zika virus infection is transmitted by the bite of Aedes sp, although transplacental transmission to the fetuse has also been described. Congenital microcephaly is the first finding related to the disease and is associated with defects in neuronal proliferation and death of cortical progenitor cells, which result in a decrease in neuronal production and a group of brain disorders which compromise motor skills, vision, hearing and cognitive functions. The present study describes the epidemiological, clinical and imaging characteristics in pediatric patients with microcephaly secondary to suspected Zika virus infection who attended the Neuropediatric consultation of the Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga during the December 2016-September 2017 period.
Keywords: epidemiology; clinical; imaging; microcephaly; Zika virus